Tres especies nuevas de Stachys (Labiatae) de México - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 1988)
Three Mexican species of Stachys are described as new: S. herrerana, from the state of Hidalgo, as well as S. langmaniae and S. vulnerabilis, from Nuevo León. S. herrerana seems to be similar to S. venulosa Greene, known from Durango, while S. langmaniae and S. vulnerabilis are perhaps related to each other, but their affinities with other species are obscure.